Supramolecular Networks Obtained by Block Copolymer Self-Assembly in a Polymer Matrix: Crystallization Behavior and Its Effect on the Mechanical Response - Schmarsow, Ruth Noemí (2023)
In recent years, there has been growing interest in the study of supramolecular networks obtained by self-assembly of amphiphilic molecules due to their responsive behavior to different external stimuli. The possibility of embedding supramolecular networks into polymer matrices opens access to a new generation of functional polymers with great potential for various applications. However, very little is known about how the dynamics of the supramolecular network is affected by diffusional and topological limitations imposed by the polymer matrix. In this work, we investigate the behavior of supramolecular networks embedded into a rubbery polymer. Crystallization-driven self-assembly of a poly(ethylene-block-ethylene oxide) (PE-b-PEO) diblock copolymer was used to generate supramolecular networks in dimethacrylate monomers, which were then photopolymerized at room temperature. PE-b-PEO self-assembles into nanoribbons with a semicrystalline PE core bordered by coronal chains of PEO, and the nanoribbons, in turn, bundle into lamellar aggregates with an average stacking period of around 45 nm. The nanoribbons are interconnected through crystalline nodes in a 3D network structure. Small-angle X-ray scattering experiments show that the polymer matrix preserves the structure of the supramolecular network and avoids its disintegration when the material is heated above the melting temperature of PE cores. Successive self-nucleation and annealing studies reveal that the polymer matrix does not influence the crystallization-melting processes of PE, which take place through the interconnected cores of the supramolecular network. In contrast, the matrix imposes strong effects of topological confinement on the crystallization of PEO, limiting the dimensions of the crystalline lamellae that can be formed. Mechanical tests show that the deformation capacity of these materials can be precisely tuned by programming the temperature within the melting range of the supramolecular network. This behavior was also characterized by shape memory cyclic tests.